LEVERAGING VIDEO PRODUCTION CLASS ACTIVITIES TO ENHANCE PROJECT-BASED LEARNING IN PRODUCTION ADVERTISING SUBJECT - Afeez Nawfal; Ammalina Dalillah; Ramlan Jantan; Khairol Ezedy; Zaharatul Mardhiah; Mohamad Yusob, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study investigates how video production activities in a Production Advertising class can effectively utilize Project-Based Learning (PBL) to enhance student engagement and skill acquisition, grounded in the principles of Constructivist Learning Theory. Constructivism emphasizes that learners build knowledge through active, authentic, and social experiences. Within this framework, the study explores how video-based projects simulate real-world challenges, promote reflective inquiry, and bridge theoretical knowledge with practice. Adopting a qualitative phenomenological design, data were collected using Colaizzi’s seven-step method through in-depth interviews with six student groups and two instructors, as well as classroom observations and analysis of student-produced advertising video product. Findings reveal several emergent themes from the experiences of both instructors and students. Overall, the study underscores the transformative potential of PBL grounded in constructivist theory to foster active, meaningful, and industry-relevant learning in creative media education. By replacing passive lecture-based instruction with authentic, project-driven tasks, instructors can promote critical thinking, practical engagement, and professional readiness. These findings advocate for learner-centred pedagogies that mirror real-world production environments while cultivating essential 21st-century skills.